Dental Caries in Children and The Role of Parents in its Prevention - Muthia Syukma Pertiwi; Deaf Wahyuni Ramadhani; Hendra Suherman (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Dental health plays an important role, especially in child development, because dental problems in early childhood can affect tooth growth in the future. Cavities, which in medical terms are called dental caries, are one of the diseases that often occur in the teeth and mouth. The World Health Organization (WHO) reports that 60 to 90 percent of children in schools around the world experience tooth decay. Information from the Indonesian Dentists Association shows that at least 89 percent of cases of dental caries occur in young children. For this reason, the role of parents is needed in this case to prevent cavities in children. Review: Cavities are a condition in which the outermost to the deepest layer of the teeth (damaged by microorganisms that can ferment carbohydrates, resulting in acidic oral conditions. Parents have a very important role in maintaining the health of their children's teeth and mouths. A study shows that psychological and social factors of parents, such as maternal depression, low communication between family members, excessive attention, and stress, can harm children's oral health. Conclusion: Oral health is a public health issue that must be addressed immediately before the problem becomes more serious. Dental health plays an important role, especially in child development, because dental disorders at an early age can affect tooth growth in the future.